Aksi Peduli Lindungi: Kegiatan Membersihkan Pantai Kunyit Kecamatan Bumi Waras Kota Bandar Lampung - Febiola Putri Giska Mutiara; Nugroho Adhi Puspito; Nisa Aprilliani; Galang Samudra; Reza Aulia; Ayunda Rahmanita Ahmad; Tria Ratna Wulandari; Toto Gunarto; Zulfa Emalia (Masyarakat Ekonomi Syariah Bogor, 2024)
The cleanliness condition of Kunyit Beach, Bumi Waras sub-district, has recently become increasingly concerning, with a lot of litter scattered around and no one willing to clean it up. There is trash caught in the rocks along the beach, most of which is inorganic waste such as plastic, bottles, styrofoam, and other discarded items, as well as some organic waste like wood and leaves. This is caused by the lack of public awareness about the importance of maintaining cleanliness and the absence of government support, such as the lack of adequate waste disposal facilities and Environmental Cleanliness Operations Units. (SOKLI). Therefore, a care and protection action was carried out to address the issues arising in the Kunyit Beach area. Environmental care actions through beach cleaning activities are a concrete effort to preserve marine and coastal ecosystems, as well as to raise public awareness about the importance of a clean environment. This action was carried out by the local community who voluntarily assisted, as well as members of Group 1 of the Natural Resources and Environmental Economics course, to fulfill the assignment given by the course instructor, with permission from the Head of the Development Economics Department, the District Head of Bumi Waras, and the Village Head of Bumi Waras. Through this action, it is hoped that collective awareness will be created to maintain environmental cleanliness and the habit of not littering so that coastal areas can be sustainably preserved.